2009
DOI: 10.4314/jasem.v11i1.46827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of semen extenders on the motility and viability of stored African Catfish (Clarias gariepinus) spermatozoa

Abstract: This study assessed the effects of common extenders and diluents on the spermatozoa of African catfish (Clarias gariepinus), with the intent of obtaining a semen preservation protocol that can serve as a means of making fingerlings available to fish farmers all year round. Semen samples (milt) were pooled from mature broodstock males and pre-extension qualities were evaluated. Egg yolk, tomato juice and sodium citrate buffers were combined in four different trials and used to preserve obtained semen at tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
2
8
0
1
Order By: Relevance
“…Previous reports also corroborate the line of thought of this study; improved survival rate of spermatozoa preserved with tomato juice at 5°C was observed in African catfish (Clarias gariepinus; Adeyemo et al 2007). In addition, Al-Daraji (2012) reported the protective effect of orange juice on spermatozoa against the harmful effects of lipid peroxidation in white layer cocks' semen.…”
Section: Quality and Fertility Of Rabbit Semen Diluted With Watermelosupporting
confidence: 90%
“…Previous reports also corroborate the line of thought of this study; improved survival rate of spermatozoa preserved with tomato juice at 5°C was observed in African catfish (Clarias gariepinus; Adeyemo et al 2007). In addition, Al-Daraji (2012) reported the protective effect of orange juice on spermatozoa against the harmful effects of lipid peroxidation in white layer cocks' semen.…”
Section: Quality and Fertility Of Rabbit Semen Diluted With Watermelosupporting
confidence: 90%
“…This value is in agreement with the suggested pre-extension motility of 80% and above (Akay et al, 1995;Urbanyi et al, 1999;Adeyemo et al, 2007). The poor result obtained in the test group following storage can be attributed to some factors one of which could be the repeated effect of freezing and thawing.…”
Section: Discussionsupporting
confidence: 89%
“…It is well known that Na citrate has the ability to preserve milt of Clarias gariepinus when refrigerated (Mansour et al, 2005;Adeyemo et al, 2007), thus it served as the control in this research. Results obtained showed that Na citrate at 4°C gave 20% motility and viability by day 7 post storage.…”
Section: Discussionmentioning
confidence: 99%
“…The fruit-juice was prepared according to the procedure by Adeyemo et al (2007) with some modifications as follows: fresh cucumber, pineapple and orange were washed thoroughly using distilled water. The fruits were first peeled (pineapple and orange) and thereafter cut into pieces and the seeds were removed (cucumber and orange) and then the fruit were blended for five minutes, placed in a sieve and pressure was applied manually to squeeze the juice out from the blended fruits.…”
Section: Juice Preparationmentioning
confidence: 99%
“…Cucumber (Cucumis sativus), pineapple (Ananas comosus) and orange (Citrus sinensis) are fruit-rich natural antioxidants renowned for their high concentrations of these vitamins and other antioxidants (Cutler et al, 2008). Improved survival rate of spermatozoa preserved with tomato juice at 5°C was observed in African catfish (Clarias gariepinus; Adeyemo et al, 2007). In addition, Al-Daraji (2012) reported the protective effect of orange juice on spermatozoa against the harmful effects of lipid peroxidation of white layer cocks' semen stored for up to 72 h. Daramola and Adekunle (2015) recently observed improved progressive motility, acrosome and membrane integrities, reduced abnormalities and MDA following supplementation of extenders with pineapple and cucumber juices during refrigeration of semen obtained from WAD goat bucks.…”
Section: Introductionmentioning
confidence: 99%